How Public Relations Perceived (SWOT Model Analysis) - Ayu Sulistya Putri Sugeng; Janah, Raisatul; Febrina Yusar (JURNAL KOMUNIKATIO, 2022)
ABSTRACT Purpose: This paper aims to understand the challenge of Public Relations, to face the society perception/reputation towards Public Relations. By understanding what is the SWOT of Public Relations when they play their role among society. Design/Methodology Approach: This paper will be a literature review of some source of scientific writing which the writer will elaborate 8 published journals related to the issue this paper talks about. Finding: Visible aspects such as appearance of PR practitioner, Educational background and communication skill is more considered on developing countries’ public. On the other hand invisible aspects such as strategic-thinking skills, analyzing and listening skills are merely needed on developed countries’ public perceptions. Research Limitations: Due to literature review process, the writer cannot directly provides a premier data about the related phenomena, yet the writer only serve data and findings that the previous published journals have found. Therefore, the writer will generated information from those journals to encompass the reader towards better understanding on PR’s reputation on both PR Practitioners and Public’s opinion. Practical Implications: This writing will help PR in the future to forecast their SWOT and optimize their Strength, minimize their Weakness, Seeking for the best Opportunity and encounter Threats as PR Practitioners. Value/Originality: Will enriched the insights of how PR perceives and how PR should do to deal with the challenges. Keywords: Public Relations, Communication, Reputation, SWOT Model, Gender Paper Type: Literature Review